Efek Protektif Suplementasi Ekstrak Etanol Daun Seri (Muntingia calabura) Terhadap Perubahan Histologis Pankreas Tikus Yang Diinduksi Diet Tinggi Lemak - Mukhyarjon Mukhyarjon; Irwan Irwan; Ismawati Ismawati (Jurnal Ilmu Kedokteran, 2026)
Diabetes mellitus is a major global health problem. Lipotoxicity is a key cause of insulin resistance that ultimately leads to pancreatic damage in type 2 diabetes mellitus. One plant with potential to prevent pancreatic damage is the Seri plant (Muntingia calabura). This study aimed to analyze the effect of ethanolic extract of Muntingia calabura leaves on pancreatic damage in rats induced by a high-fat diet (HFD). This was an experimental study with a post-test-only design. A total of 28 male Wistar rats weighing 120–200 grams were divided into four groups: K1 received standard feed (20 g/rat/day) and water ad libitum; K2 received a 50% high-fat diet (20 g/rat/day); K3 received the same HFD plus Muntingia calabura leaf extract (100 mg/kg/day); and K4 received HFD plus pioglitazone (6 mg/kg/day). Treatments were administered for 8 weeks, followed by termination for pancreatic histological examination. The variables studied were supplementation of Muntingia calabura ethanolic extract and the degree of pancreatic insulitis. Histological preparations were stained with hematoxylin-eosin, and insulitis was scored. Data were analyzed using IBM SPSS with Kruskal–Wallis and Mann-witney tests. Results showed no insulitis in K1, while mild insulitis was observed in K2, K3, and K4. A significant difference in histological scores was found between K1 and K2 (p = 0.03), whereas no significant differences were observed among other groups. In conclusion, 8 weeks of HFD induced mild insulitis in rats, while Muntingia calabura leaf extract and pioglitazone did not demonstrate protective effects against insulitis.